Generated Un-detectability Covert Channel Algorithm for Dynamic Secure Communication Using Encryption and Authentication - Fatayer, Tamer S. A. (2017 Palestinian International Conference on Information and Communication Technology (PICICT), 2017)
The keys generated by (symmetric or asymmetric) have been still compromised by attackers. Cryptography algorithms need extra efforts to enhance the security of keys that are transferring between parities. Also, using cryptography algorithms increase time consumption and overhead cost through communication. Encryption is very important issue for protecting information from stealing. Unfortunately encryption can achieve confidentiality not integrity. Covert channel allows two parties to indirectly send information, where the main drawbacks of covert channel are detectability and the security of pre-agreement knowledge. In this paper, i merge between encryption, authentication and convert channel to achieve un-detectability covert channel. This channel guarantee integrity and confidentiality of covert data and sending data dynamically. I propose and implement un-detectability a covert channel using AES (Advanced Encryption Standard) algorithm and HMAC (Hashed Message Authentication Code). Where this channel is un-detectability with integrity and confidentiality agreement process between the sender and the receiver. Instead of sending fake key directly through channel, encryption and HMAC function used to hide fake key. After that investigations techniques for improving un-detectability of channel is proposed.